Dispositivo para conservación del tono muscular en niños con síndrome de Down (2022)
This document presents the project to a degree in which different elements are taken into account to reach a possible solution to a problem described in the following question (how from industrial design can we contribute to reducing the negative impact that hypotonia in pediatric rehabilitation of upper limbs in children with down syndrome?). Contemplating the different scopes may have in this work, an investigation is carried out, synthesis, construction of regulations, requirements and determinants, referents, aesthetic, communicative and functional construction to make a proposal. From the data found in different magazines, diagrams and books, results were obtained consistent that gave rise to a substantive process.The product to be developed is a therapeutic device which will lead to preserve the tone muscles of the upper limbs, consists of 6 aliens which they will come to help them to make their therapies more fun and playful, these will spread out in a large mat which will have 4 levels that the child must complete in order to finish with their respective therapy, there will be 6 friends who will be accompanying them who will have different targets on children's muscles.